Utility of Circadian Variability Patterns in Differentiating Origins of Premature Ventricular Complexes - Mu Chen; Qunshan Wang; Jian Sun; Peng-Pai Zhang; Wei Li; Rui Zhang; Bin-Feng Mo; Tai-Zhong Chen; Juyi Wan; Dong-Zhu Xu; Kazutaka Aonuma; Yi-Gang Li (Journal of Interventional Cardiology)
Background. Premature ventricular complexes (PVCs) exhibit circadian fluctuation. We determine if PVCs of different origin exhibit specific circadian patterns. Methods. We analyzed Holter recordings from patients with monomorphic PVCs who underwent catheter ablation. PVC circadian patterns were classified as fast-heart rate- (HR-) dependent (F-PVC), slow-HR-dependent (S-PVC), or HR-independent (I-PVC). PVC origins were determined intraprocedurally. Results. In a retrospective cohort of 407 patients, F-PVC and S-PVC typically exhibited diurnal and nocturnal predominance, respectively. Despite decreased circadian fluctuation, I-PVC generally had heavier nocturnal than diurnal burden. PVCs of left anterior fascicle origin were predominantly S-PVC, while those of posterior hemibranch origin were mostly F-PVC. PVCs originating from the aortic sinus of Valsalva (ASV) were predominantly I-PVC, while most PVCs arising from the left ventricular outflow tract (LVOT) were F-PVC. Using a diurnal/nocturnal PVC burden ratio of 0.92 as the cutoff value to distinguish LVOT from ASV origin achieved 97% sensitivity and, as further verification, an accuracy of 89% (16/18) in a prospective cohort of patients with PVCs originating from either ASV or LVOT. In contrast, PVCs originating from right ventricles, such as right ventricular outflow tract, did not show distinct circadian patterns. Conclusions. The circadian patterns exhibit origin specificity for PVCs arising from left ventricles. An analysis of Holter monitoring provides useful information on PVC localization in ablation procedure planning.